A public health response to the methamphetamine epidemic: the implementation of contingency management to treat methamphetamine dependence - Hare C Bradley; Stansell John; Tierney Stephen; Reback Cathy J; Klausner Jeffrey D; Shoptaw Steven; Gibson Steven; Siever Michael; King William D; Kao Uyen; Dang Jeffrey (BMC Public Health, 2006)
Abstract Background In response to increases in methamphatemine-associated sexually transmitted diseases, the San Francisco Department of Public Health implemented a contingency management (CM) field program called the Positive Reinforcement Opportunity Project (PROP). Methods Methamphetamine-using men who have sex with men (MSM) in San Francisco qualified for PROP following expressed interest in the program, provision of an observed urine sample that tested positive for methamphetamine metabolites and self-report of recent methamphetamine use. For 12 weeks, PROP participants provided observed urine samples on Mondays, Wednesdays and Fridays and received vouchers of increasing value for each consecutive sample that tested negative to metabolites of methamphetamine. Vouchers were exchanged for goods and services that promoted a healthy lifestyle. No cash was provided. Primary outcomes included acceptability (number of enrollments/time), impact (clinical response to treatment and cost-effectiveness as cost per patient treated). Results Enrollment in PROP was brisk indicating its acceptability. During the first 10 months of operation, 143 men sought treatment and of these 77.6% were HIV-infected. Of those screened, 111 began CM treatment and averaged 15 (42%) methamphetamine-free urine samples out of a possible 36 samples during the 12-week treatment period; 60% completed 4 weeks of treatment; 48% 8 weeks and 30% 12 weeks. Across all participants, an average of $159 (SD = $165) in vouchers or 35.1% of the maximum possible ($453) was provided for these participants. The average cost per participant of the 143 treated was $800. Conclusion Clinical responses to CM in PROP were similar to CM delivered in drug treatment programs, supporting the adaptability and effectiveness of CM to non-traditional drug treatment settings. Costs were reasonable and less than or comparable to other methamphetamine outpatient treatment programs. Further expansion of programs like PROP could address the increasing need for acceptable, feasible and cost-effective methamphetamine treatment in this group with exceptionally high rates of HIV-infection.